2017
DOI: 10.1016/j.chom.2017.05.009
|View full text |Cite
|
Sign up to set email alerts
|

IL-22 Upregulates Epithelial Claudin-2 to Drive Diarrhea and Enteric Pathogen Clearance

Abstract: SUMMARY Diarrhea is a host response to enteric pathogens, but its impact on pathogenesis remains poorly defined. By infecting mice with the attaching and effacing bacteria Citrobacter rodentium, we defined the mechanisms and contributions of diarrhea and intestinal barrier loss to host defense. Increased permeability occurred within 2 days of infection and coincided with IL-22-dependent upregulation of the epithelial tight junction protein claudin-2. Permeability increases were limited to small molecules, as e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
200
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 192 publications
(218 citation statements)
references
References 33 publications
9
200
3
Order By: Relevance
“…Early after infection with C. rodentium (and potentially also upon infection by other attaching‐and‐effacing bacteria) an IL‐22‐dependent innate immune response leads to upregulation of claudin‐2 expression in the colonic epithelium, resulting in efflux of water into the lumen, enabling a swift diarrheal response which expedites bacterial clearance . Importantly, C. rodentium infection also promotes processes leading to leak of larger substances, including bidirectional, unrestricted leak stemming from damage to the epithelial layer.…”
Section: Ilc As Guardians Of Tissue Homeostasis Epithelial Remodelinmentioning
confidence: 99%
“…Early after infection with C. rodentium (and potentially also upon infection by other attaching‐and‐effacing bacteria) an IL‐22‐dependent innate immune response leads to upregulation of claudin‐2 expression in the colonic epithelium, resulting in efflux of water into the lumen, enabling a swift diarrheal response which expedites bacterial clearance . Importantly, C. rodentium infection also promotes processes leading to leak of larger substances, including bidirectional, unrestricted leak stemming from damage to the epithelial layer.…”
Section: Ilc As Guardians Of Tissue Homeostasis Epithelial Remodelinmentioning
confidence: 99%
“…IL‐22 also affects the glycosylation of IEC surface proteins by inducing fucosyltransferase 2 (Fut2) expression, thereby enhancing host protection against Salmonella Typhimurium . Mucin production by IECs is also increased by IL‐22 through the activation of signal transducer and activator of transcription STAT3, and tight junction proteins such as claudin‐2 have recently been shown to be up‐regulated by IL‐22, inducing diarrhoea and facilitating clearance of Citrobacter rodentium in a mouse model of enteric infection …”
Section: Iec–immune Cell Crosstalkmentioning
confidence: 99%
“…99 Mucin production by IECs is also increased by IL-22 through the activation of signal transducer and activator of transcription STAT3, 100 and tight junction proteins such as claudin-2 have recently been shown to be up-regulated by IL-22, inducing diarrhoea and facilitating clearance of Citrobacter rodentium in a mouse model of enteric infection. 101 Beyond ILC3s and IL-22, some other lymphoid cells also contribute to IEC responses. During parasitic infection, IECs secrete a number of cytokines that promote the expansion and activation of group 2 innate lymphoid cells (ILC2s) and basophils, including IL-33 and thymic stromal lymphopoietin (TSLP), and IL-25 produced by tuft cells.…”
Section: Immune Cell Contributions To Iec Differentiation and Functionmentioning
confidence: 99%
“…Previous studies have revealed the important role of certain CLDN in physiological regulation of junction permeability in a variety of tissues, and the epithelial barrier dysfunction, resulting from deficiency of CLDN, plays a crucial role in the development of various disorders (e.g. atopic dermatitis) . However, no study has yet examined the expression of CLDN in lesional skin of patients with rosacea, or investigated the correlation between CLDN and the development of rosacea.…”
Section: Introductionmentioning
confidence: 99%
“…atopic dermatitis). 20,[23][24][25] However, no study has yet examined the expression of CLDN in lesional skin of patients with rosacea, or investigated the correlation between CLDN and the development of rosacea. Therefore, the aim of this study was to describe the expression of CLDN in lesional skin of patients with rosacea compared with healthy skin, and determine the possible relationship between CLDN and the development of rosacea.…”
Section: Introductionmentioning
confidence: 99%